(untitled) (The Review of Diabetic Studies, 2025)
Background: Diabetic peripheral neuropathy (DPN) is a common microvascular complication of type 2 diabetes mellitus (T2DM) and a leading cause of foot morbidity. Nerve conduction studies (NCS) remain the reference standard but are time-consuming and assess predominantly large fibers. Shear wave elastography (SWE) enables non-invasive quantitative assessment of nerve stiffness. This study evaluated the diagnostic performance of tibial nerve SWE alone and in combination with the Toronto Clinical Scoring System (TCSS) in detecting DPN. Methods: In this prospective observational study, 60 patients with T2DM were enrolled over one year. Participants were categorized into DPN and non-DPN groups based on NCS findings. All subjects underwent TCSS evaluation, conventional ultrasonography for tibial nerve cross-sectional area (CSA), and SWE to obtain Emean, Emin, and Emax values bilaterally. Group comparisons, correlation analysis, and receiver operating characteristic (ROC) analysis were performed. Results: Tibial nerve stiffness parameters were significantly higher in the DPN group compared to the non-DPN group (p < 0.01). Mean right tibial nerve stiffness (Emean RT) demonstrated excellent diagnostic performance (AUC = 0.932; 95% CI: 0.872–0.993). SWE parameters showed strong positive correlation with TCSS scores (r ≈ 0.79, p < 0.01). Combining SWE with TCSS improved diagnostic sensitivity and specificity compared with either modality alone. Conclusion: Tibial nerve SWE is a reliable non-invasive imaging biomarker for DPN. When combined with TCSS, diagnostic accuracy improves significantly. SWE may serve as a practical adjunct screening tool in patients with T2DM.